ROLE OF ELECTRONIC INSTRUMENTS IN MUSIC TEACHING AND PERFORMANCE: संगीत शिक्षण एवं प्रदर्शन में इलेक्ट्रानिक वाद्य यंत्रों की भूमिका - Pandey, Durgesh (International Journal of Research -GRANTHAALAYAH, 2015)
The smallness of the sound is based on intensity. When it affects the brain and the heart, first blood activity is affected and then it is transformed into mental sensation. To measure the intensity of noise, we use the decibel method. It is also known as Phan; It is worth noting here that if the sound level of a flute produced by a flute is 40 fane, the level of the sound of the two flutes would be only about 43 pans instead of 80 pans and the sound level of 10 flutes would be around 50 pans. There is a difference in the intensity of the sound and not the highness of it. नाद का छोटा-बड़ापन तीव्रता पर आधारित होता है। इसका प्रभाव मस्तिष्क और हृदय पर जब पड़ता है तो पहले रक्त क्रिया प्रभावित होती है और उसके बाद मानसिक अनुभूति के रूप में उसका रूपांतर होता है। नाद की तीव्रता नापने के लिए डेसीबल पद्धति को अपनाते हैं। इसे फाॅन ;च्ींदद्ध नाम से भी जाना जाता है, जिसके आधार पर साधारण बातचीत की ध्वनि का क्षेत्र 60 से 70 फाँन के मध्य में रहता है। यहाँ यह बात ध्यान देने योग्य है कि यदि एक बाँसुरी से उत्पन्न नाद का ध्वनि स्तर 40 फाॅन है तो दो बाँसुरियों के सम्मिलित नाद का स्तर 80 फाॅन न होकर केवल 43 फाॅन के लगभग होगा और 10 बाँसुरियों का नाद स्तर 50 फाॅन के लगभग होगा। नाद की तीव्रता में अंतर आता है न कि उसके ऊँचे-नीचेपन में।